EFFECTS OF HEAVY METAL TOXICITY ON MAZE SEEDLINGS GROWTH TRAITS - Shafique, F; Ali, Q; Malik, A (Biological and Clinical Sciences Research Journal, 2020)
Maize is an edible cereal crop that belongs to family Gramineae and use as an energy source for human and animals. In our country the industrial and municipal wastewater has been being used for irrigation purposes that contain heavy metals. These heavy metals affect production of maize crop and soil quality. The purpose of this study was to investigate the affect of different heavy metals on maize growth and to asses more tolerant and more sensitive maize variety. Different concentrations of Mn and Cr (0, 0.25Molar, 0.50Molar) were applies in combined form and individually. Total three replicates were carried out during research. Analysis of variance (ANOVA), Tukey’s rang test (p ≤ 0.05) were applied as statistical tool among treatment means. ANOVA indicated the differences among five different genotypes and 9 different treatments for all parameters were significant. Tukey’s test indicated that higher toxic effect was shown under treatment 0.5M Mn + 0.25M Cr while less toxic effect was observed under treatment 0.50M Mn in maize plant. The genotype 31R88 was more sensitive for metal toxicity because most of 31R88 traits were affected under heavy metal treatments while more tolerant variety was Neelum. Hence the results of our study have suggested that the genotype Neelum may be used for the improvement of grain yield and productivity under heavy metal stress conditions.